Prevalence of Colonization with Multidrug-Resistant Bacteria: Results of a 5-Year Active Surveillance in Patients Attending a Teaching Hospital - Angela Quirino; Claudia Cicino; Giuseppe Guido Maria Scarlata; Nadia Marascio; Gianfranco Di Gennaro; Giovanni Matera; Francesca Licata; Aida Bianco (Antibiotics, 2023)
Combating antimicrobial resistance (AMR) requires comprehensive efforts, such as screening to identify patients colonized by multidrug-resistant microorganisms (MDROs). The primary purpose of this study was to estimate the AMR pattern of methicillin-resistant Staphylococcus aureus (MRSA) isolated from nasal surveillance swabs and MDROs isolated from pharyngeal and rectal surveillance swabs in patients attending a teaching hospital. Data were sought retrospectively, from 1 January 2017 to 31 December 2021, from the records produced by the hospital microbiology laboratory. Duplicate isolates, defined as additional isolates of the same microorganism with identical antibiograms, were excluded. Among Staphylococcus aureus isolates from nasal swabs, 18.2% were oxacillin-resistant. Among Gram-negative bacteria, 39.8% of Klebsiella pneumoniae and 83.5% of Acinetobacter baumannii isolates were carbapenem-resistant. Resistance to three antibiotic categories was high among Acinetobacter baumannii (85.8%) and Klebsiella pneumoniae (42.4%). The present data highlight a high prevalence of MDRO colonization among patients admitted to the hospital and suggest that screening for MDROs could be an important tool for infection control purposes, especially in geographical areas where limiting the spread of MDROs is crucial. The results also underline the importance of active surveillance, especially for carbapenem-resistant, Gram-negative bacteria in reducing their transmission, especially in high-risk units.